2000
DOI: 10.1016/s0042-6989(00)00059-6
|View full text |Cite
|
Sign up to set email alerts
|

The importance of sustained attention for patients with maculopathies

Abstract: Sustained attention enhances perception in eccentric positions in the visual field, which helps patients with foveal vision loss to develop a peripheral 'preferred retinal locus' (PRL). Besides central scotoma topography, local variations of attentional performance could influence the choice of PRL location. We tested sustained attention augmenting peripheral letter recognition in 23 maculopathy patients and 15 normally-sighted subjects (eight positions, 8 degrees eccentricity). Performance was shown to depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
2
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 16 publications
6
98
2
2
Order By: Relevance
“…A t test (p < .05) performed on the PFs of each frame orientation (horizontal or vertical) revealed larger PF for the frame presented in the horizontal (44 ms) than in the vertical orientation (34 ms, t(7) = 2.581; p = .04). These findings are similar to results of studies that have used RT tasks and have suggested different distributions of attention between the two meridians with greater concentration of attention on the horizontal than on the vertical meridian (Altpeter, Mackeben, & Treuzettel-Klosinski, 2000;Galera et al, 2005;Panagopoulos et al 2004). However, results manipulating visual restrictions and the displacement of attention indicate that such differences can be caused by visual factors, independent of the distribution of attention (Carrasco, Talgar, & Cameron, 2001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A t test (p < .05) performed on the PFs of each frame orientation (horizontal or vertical) revealed larger PF for the frame presented in the horizontal (44 ms) than in the vertical orientation (34 ms, t(7) = 2.581; p = .04). These findings are similar to results of studies that have used RT tasks and have suggested different distributions of attention between the two meridians with greater concentration of attention on the horizontal than on the vertical meridian (Altpeter, Mackeben, & Treuzettel-Klosinski, 2000;Galera et al, 2005;Panagopoulos et al 2004). However, results manipulating visual restrictions and the displacement of attention indicate that such differences can be caused by visual factors, independent of the distribution of attention (Carrasco, Talgar, & Cameron, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…Similar results of RT tasks suggest that the larger advantage found for the horizontal meridian can be the product of a greater distribution of attention along this meridian (Altpeter et al, 2000;Galera et al, 2005;Panagopoulos et al, 2004). But different results for a comparison of the horizontal and vertical meridians were also found by Carrasco et al (2001) who reported no difference between conditions where attention was displaced and those where it was not displaced along different meridians.…”
Section: Discussionmentioning
confidence: 77%
“…Such patients may use the functional fovea with a ring scotoma for high-acuity tasks and use an eccentric location outside of the scotoma for other tasks. Finally, as mentioned earlier, PRL placement may relate to visual attention (Altpeter et al, 2000). The multiple PRL phenomenon may have mechanisms in common with switching attention among different peripheral areas in the visual field.…”
Section: Multiple Prlsmentioning
confidence: 77%
“…He et al (1996) found that attentional resolution, the finest separation of objects that allows isolated visual attention, was better in the lower visual field compared to the upper visual field. Altpeter et al (2000) asked 22 patients with macular diseases and 15 normally sighted participants to report the orientation (among 4 choices) of the character E at cued and attended locations in different parts of the visual field. Overall, the horizontal meridians yielded better performance than the vertical meridians.…”
Section: Performance-driven Explanation Of Prlmentioning
confidence: 99%
“…Previous studies have attributed the HVA (Altpeter et al, 2000;Mackeben, 1999) and VA (Altpeter et al, 2000) to sustained attention. Given that the transient component of attention is considered to operate at an earlier stage of visual processing than the sustained component(e.g., Nakayama & Mackeben, 1989), before an attentional explanation is invoked, it is important to rule out the likely possibility-and more parsimonious explanation-that visual constraints also underlie the performance fields.…”
Section: Discussionmentioning
confidence: 94%